2015
DOI: 10.1101/lm.038000.114
|View full text |Cite
|
Sign up to set email alerts
|

Impact of adolescent sucrose access on cognitive control, recognition memory, and parvalbumin immunoreactivity

Abstract: In this study we sought to determine the effect of daily sucrose consumption in young rats on their subsequent performance in tasks that involve the prefrontal cortex and hippocampus. High levels of sugar consumption have been associated with the development of obesity, however less is known about how sugar consumption influences behavioral control and high-order cognitive processes. Of particular concern is the fact that sugar intake is greatest in adolescence, an important neurodevelopmental period. We provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
75
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 78 publications
8
75
2
1
Order By: Relevance
“…Fast-spiking parvalbuminpositive GABAergic interneurons regulate early phases of adult hippocampal neurogenesis (Song et al 2013). Previously, we observed a reduction in parvalbumin neuron immunoreactivity within the dorsal hippocampus of rats that consumed sucrose on a daily basis (Reichelt et al 2015a), which may have contributed to the reduced neuroproliferation markers observed here.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…Fast-spiking parvalbuminpositive GABAergic interneurons regulate early phases of adult hippocampal neurogenesis (Song et al 2013). Previously, we observed a reduction in parvalbumin neuron immunoreactivity within the dorsal hippocampus of rats that consumed sucrose on a daily basis (Reichelt et al 2015a), which may have contributed to the reduced neuroproliferation markers observed here.…”
supporting
confidence: 52%
“…Furthermore, these detrimental effects can be long lasting. For example, we (Reichelt et al 2015a) recently demonstrated that rats who consumed 10% sucrose for 2 h a day across their adolescence exhibited object-in-place memory deficits assessed 6 wk after cessation of sucrose access. Memory involves not only remembering information over time, but also keeping memories distinct and minimizing interference among them.…”
mentioning
confidence: 99%
“…Results revealed sucrose-associated deficits in object-in-place task, which tests hippocampal-dependent episodic contextual memory. In this study access to the diet ended at the end of the adolescent period and the testing was performed during adulthood 5-weeks after the last sucrose treatment [45]. …”
Section: Juvenile and Adolescent Periodmentioning
confidence: 99%
“…We and others have also demonstrated significant deleterious effects on hippocampal function specifically following adolescent consumption of a high-fat diet (HF) and/or high-sugar diet. Rodents that consume a diet supplemented with fat and/or sugar throughout adolescence, but not during adulthood, show impaired performance on a range of hippocampal-dependent behavioral tasks including object location memory (Valladolid-Acebes et al, 2013; Reichelt et al, 2015), spatial memory (Boitard et al, 2014; Hsu et al, 2015; Klein et al, 2016) and relational memory (Boitard et al, 2012). These cognitive deficits are associated with overexpression of hippocampal pro-inflammatory cytokines (Boitard et al, 2014; Hsu et al, 2015) and decreased levels of hippocampal neurogenesis (Boitard et al, 2012).…”
Section: Introductionmentioning
confidence: 99%